1999
DOI: 10.1002/(sici)1099-1395(199904)12:4<340::aid-poc120>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of oxidation of 1,10‐phenanthroline by alkaline permanganate

Abstract: The kinetics of the oxidation of 1,10-phenanthroline (1,10-phen) by permanganate were investigated in alkaline medium. A first-order, fractional-order and zero-order dependence of the rate each in [MnO 4 À ], [1,10-phen] and [OH À ], respectively, was observed. The data suggest that the oxidation proceeds via the formation of a complex between 1,10-phen and MnO 4 À which decomposes in a slow step to yield the free radical of 1,10-phen, followed by a fast step to give 2,2'-bipyridy1 3,3'-dicarboxaldehyde. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Similar results have been observed in the phenanthroline complexes of various metals (28–30) and for the free ligands (18). It would appear that the hyperconjugative interactions of the methyl groups are greatest at the 5, 6 positions, which are also the most easily oxidized positions of the phenanthroline ring (31–33).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been observed in the phenanthroline complexes of various metals (28–30) and for the free ligands (18). It would appear that the hyperconjugative interactions of the methyl groups are greatest at the 5, 6 positions, which are also the most easily oxidized positions of the phenanthroline ring (31–33).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments with model compounds such as amino acids (e.g., [11][12][13][14] have shown that the reduction of permanganate by these species at high pHs proceeds via formation of manganate MnO4 2-, hypomanganate MnO4 3-(15), and finally MnO2 or mixed Mn(III)/Mn-(IV) solids (16). Identified reaction products formed upon the permanganate oxidation of amino acids and other model compounds include ammonia, oxalate, CO2, and traces of aldehydes (17)(18)(19)(20). Similar species and, in addition to them, IDA, glycine, and glycolate were identified in solutions of EDTA oxidized at high pHs by Ag(III) (21), and also at circumneutral pHs in the case of oxidation by hydroxyl radicals generated in the H2O2/UV system (22) or with reactive oxygen species activated by zerovalent iron (23).…”
Section: Introductionmentioning
confidence: 99%
“…The process Mn(VII)-» Mn(IV) can be divided into a number of partial steps and examined seperately. If [OH"] > 0.1 mol dm -3 , permanganate will be reduced to manganate in the first step and, owing to its much lower reactivity, further reaction with manganate will be much slower [5,6,7]. The Mn02 appears practically only after permanganate has completely disappeared from the system.…”
Section: Introductionmentioning
confidence: 99%